Sue Kreitzman's low fat desserts - Kreitzman, Sue (Piatkus, 1999)
For many people a meal is not complete without dessert. If you are weight or health conscious, the options have been limited to yogurt or fruit. For dessert lovers everywhere Sue Kreitzman has developed and perfected a mouthwatering collection of 100 low-fat dessert recipes. Included are irresistible recipes for cheesecakes, chocolate cakes, tortes, roulades, trifles, tarts, ice cream, and puddings as well as low-fat sauces, fillings, and toppings. It even includes a special Christmas section, featuring Sue's specially created low-fat Christmas pudding, cake, mince-meat and Buche de Noel.